The Euro at 22: Economic crisis and political instability - Mortágua, Mariana (2021)
This paper discusses the origins and institutional evolution of the European Monetary Union (EMU) in the light of two theoretical frameworks: the liberal federation proposed by Hayek and Robbins in the first half of the 20th century and the still prevailing neoclassical macroeconomic consensus. It is argued that before existing as Euro, the common currency was already a neoliberal project, in the sense of an ideal space for elevating market rules to a unique and definitive form of social and economic order. This neoliberal construction was technically legitimized by a neoclassical economic theory founded on wrong epistemological principles, which prevented a correct understanding of the economic and social challenges faced by the Eurozone. The result is a crisis prone configuration that will keep endangering EMU’s political and economic stability.